ON FATIGUE LIFE SCATTER FACTOR FOR THE AIRCRAFT STRUCTURE - GAO Chao; HE YuTing; HOU Bo; ZHANG Teng (Jixie qiangdu)
The fatigue life scatter factor is an important reliability index of the assessment of aircraft fatigue life. At present,the safe-life of a fleet is gotten by using the total test hours and the fatigue scatter factor. Usually,the environment scatter factor caused by the different service environments is not considered,and the fatigue scatter factor mainly includes two parts,one is the load scatter factor caused by the load spectrum difference of fleets; the other is the structure scatter factor caused by the difference of material and manufacturing quality. The expressions of scatter factor of fatigue life obeying the log-normal distribution and Weibull distribution are introduced and analyzed. To the situation that the structure fatigue life of the same aircraft model under different load spectrums obeys the log-normal distribution,the condition that the fatigue scatter factor is the product of the load scatter factor and the structure scatter factor is deduced. To the situation that the structure fatigue life obeys the different distributions,the service flying hours can be converted into the equivalent flying hours under the same test load spectrum based on the equal damage principle,the structure scatter factor under this spectrum can be calculated and can be taken as the fatigue life scatter factor,the safe-life calculated by this scatter factor can be seen as the reference value for the management of individual aircraft life.